2017
DOI: 10.1038/s41598-017-11726-8
|View full text |Cite|
|
Sign up to set email alerts
|

Hybrid organic-inorganic polariton laser

Abstract: Organic materials exhibit exceptional room temperature light emitting characteristics and enormous exciton oscillator strength, however, their low charge carrier mobility prevent their use in high-performance applications such as electrically pumped lasers. In this context, ultralow threshold polariton lasers, whose operation relies on Bose-Einstein condensation of polaritons – part-light part-matter quasiparticles, are highly advantageous since the requirement for high carrier injection no longer holds. Polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Hybrid polariton states were furthermore identified in structures involving organic as well as two-dimensional materials embedded in a fully metallic open cavity 107 . Such Frenkel–Wannier polaritons should be extraordinarily stable, and represent one promising candidate to observe Bosonic condensation phenomena at strongly elevated temperatures, similar to recent reports on organic-III–V hybrid excitations 108 .…”
Section: Strong Coupling In Nanostructures With Semiconducting 2d Actsupporting
confidence: 83%
“…Hybrid polariton states were furthermore identified in structures involving organic as well as two-dimensional materials embedded in a fully metallic open cavity 107 . Such Frenkel–Wannier polaritons should be extraordinarily stable, and represent one promising candidate to observe Bosonic condensation phenomena at strongly elevated temperatures, similar to recent reports on organic-III–V hybrid excitations 108 .…”
Section: Strong Coupling In Nanostructures With Semiconducting 2d Actsupporting
confidence: 83%
“…It was found that the lasing threshold of the system depends on the concentration of the dye inside the polymer matrix; the higher the concentration the lower the lasing threshold value. Polaritonic lasing has also been demonstrated for a hybrid organic–inorganic system inside an optical cavity 240. A J-aggregate forming cyanine dye and a GaAs quantum well were hybridized to a cavity mode.…”
Section: Beyond Polariton Chemistrymentioning
confidence: 97%
“…Organic semiconductors however comprise the broadest class of strongly coupled materials developed to date and include molecular dyes, crystalline organic molecules, oligofluorenes, and conjugated polymers . Owing to the high quantum yield, large dipole moment of optical transitions and high‐binding energy of excitons, organic semiconductors have permitted the physics and applications of polaritonics to be explored at room temperature .…”
Section: Introductionmentioning
confidence: 99%